C‐terminal acidic domain of histone chaperone human NAP1 is an efficient binding assistant for histone H2A‐H2B, but not H3‐H4. (4th February 2016) - Ohtomo, Hideaki; Akashi, Satoko; Moriwaki, Yoshihito; Okuwaki, Mitsuru; Osakabe, Akihisa; Nagata, Kyosuke; Kurumizaka, Hitoshi; Nishimura, Yoshifumi
Abstract : Nucleosome assembly protein 1 (NAP1) binds both the (H3‐H4)2 tetramer and two H2A‐H2B dimers, mediating their sequential deposition on DNA. NAP1 contains a C‐terminal acidic domain (CTAD) and a core domain that promotes dimer formation. Here, we have investigated the roles of the core domain and CTAD of human NAP1 in binding to H2A‐H2B and H3‐H4 by isothermal calorimetry and native mass spectrometry and compared them with the roles of yeast NAP1. We show that the hNAP1 and yNAP1 dimers bind H2A‐H2B by two different modes: a strong endothermic interaction and a weak exothermic interaction. A mutant hNAP1, but not yNAP1, dimer lacking CTAD loses the exothermic interaction and shows greatly reduced H2A‐H2B binding activity. The isolated CTAD of hNAP1 binds H2A‐H2B only exothermically with relatively stronger binding as compared with the exothermic interaction observed for the full‐length hNAP1 dimer. Thus, the two CTADs in the hNAP1 dimer seem to provide binding assistance for the strong endothermic interaction of the core domain with H2A‐H2B. By contrast, in the relatively weaker binding of hNAP1 to H3‐H4 as compared with yNAP1, CTAD of hNAP1 has no significant role. To our knowledge, this is the first distinct role identified for the hNAP1 CTAD. Abstract : The two C‐terminal acidic domains in the human NAP1 dimer provide binding‐assistance for H2A‐H2B but not H3‐H4.